Reorganização da atenção primária durante a pandemia da Covid-19: a experiência de dois municípios baianos - Cavalcante, Cleuton Machado (2023)
Primary Health Care (PHC) is the pillar that guarantees comprehensive and resolutive attention to the health of the population, in which its centrality expands the capacity of articulation with the Health Care Networks. In Brazil, the Family Health Strategy (FHS) is the main public policy implemented for the expansion and consolidation of PHC, being the preferred entrance and first level of care to promote comprehensive Health Care for the population. This attention has been altered by the COVID-19 pandemic, as PHC Services have been reorganized to meet this new challenge. This research aims to analyze the reorganization of health actions and Services of Primary Care during the COVID-19 pandemic in the municipalities of Souto Soares and Iraquara, in Bahia. This is a qualitative and descriptive research. Semi-structured interviews and document analysis were used for data collection. Fifteen people participated in the research, being six managers and nine Health workers of two FHS Units in the municipalities of Souto Soares and Iraquara - BA. The data were analyzed through the MAXQDA software, which includes all stages of Content Analysis, having the following categories: installed capacity of PHC services to cope with the COVID-19 pandemic; difficulties in the reorganization of PHC health actions and services during the COVID-19 pandemic; health actions and services implemented by PHC to cope with the COVID-19 pandemic. Despite the difficulties encountered by the services, such as: material resources, professional qualification, inadequate access, discontinuity of health care and social distancing, it was evidenced, in the face of the pandemic scenario, different strategies for reorganization of PHC, such as alteration of the operational flows and work process; monitoring of COVID-19 cases; empowering intersectoriality; innovation of specific spaces for dealing with COVID-19 cases; creation of the COVID-19 commission; elaboration of a local protocol with targeted orientations; in addition to general actions: guidance to the population, sanitary barriers, testing; and more, the use of technologies, especially the cell phone, as a way to improve users' access to health services; in addition to expanding the training and continuing education of Health workers. Thus, promoting research to implement new tools and/or strategies for the integration of services for the reorganization of PHC is an imperative need for the development of a more qualified, humane and resolutive Health Care, especially during health emergencies.